Effect of Delayed Icing on the Quality of White Shrimp (Litopenaeus vannamei) during Chilled Storage. Issue 6 (24th August 2015) - Annamalai, Jeyakumari; Sasikala, Remya; Debbarma, Jesmi; Chandragiri Nagarajarao, Ravishankar; Abubacker Aliyamveetil, Zynudheen; Ninan, George; Ronda, Venkateshwarlu; Kuttanapilly Velayudhanelayadom, Lalitha
Abstract: The effect of delayed icing on the quality of L itopenaeus vannamei was assessed by chemical, microbiological and sensory evaluation. Shrimps were divided into three lots. One lot was immediately iced and the other two lots were subjected to delayed icing after keeping in ambient conditions (30 ± 2C) for 2 and 4 h, respectively. White shrimp had a moisture content of 77.21%, protein 18.80%, ash 1.47% and fat 1.30% on wet weight basis. Total volatile basic nitrogen, trimethylamine, thiobarbituric acid and K value showed increasing trend during chilled storage. It was observed that there is a significant ( P  < 0.05) decrease in the hardness of shrimp meat during storage. Sensory evaluation indicated that the shelf life of white shrimp iced immediately after catch and 2 h delayed iced was approximately 9 days, whereas 4 h delayed iced sample had shortened shelf life of 6 days. Practical Applications: Shrimp is one of the most traded and consumed aquatic product worldwide. Shrimps are rich in protein, containing very little fat and have significant cholesterol content. Shrimp is more prone to deterioration because of its high content of free amino acids and other soluble nonprotein nitrogenous substances that can serve as easily digestible nutrients for microbial growth. Chilled or iced preservation helps in delaying or reducing the bacterial growth, preventing browning and prolonging the shelf life of shrimp. Delayed icing of the catch at the site results in downgrading of the shrimp. The present study provides information about a baseline investigation of the shelf life and quality of Pacific white shrimp due to delayed icing. It can be useful to quantify the quality and shelf life of fresh shrimp prior to the application of preservative treatments to extend the shelf life.